2017
DOI: 10.1111/acps.12822
|View full text |Cite
|
Sign up to set email alerts
|

BDNF and BMI effects on brain structures of bipolar offspring: results from the global mood and brain science initiative

Abstract: Offspring status and BMI moderate the association between BDNF levels and brain structures among bipolar offspring, underscoring BDNF regulation and overweight/obesity as key moderators of BD pathogenesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 82 publications
1
13
0
Order By: Relevance
“… 3 , 5 7 Furthermore, available data indicate that obesity differentially affects individuals with neuropsychiatric disorders, influencing illness trajectory and progression. 8 11 Notwithstanding, the mediators of the association between obesity and adverse brain function are insufficiently characterized. Replicated evidence suggests that the metabolic–immunoinflammatory interface is a critical moderator of the differential effects of obesity on individuals with a neuropsychiatric illness.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“… 3 , 5 7 Furthermore, available data indicate that obesity differentially affects individuals with neuropsychiatric disorders, influencing illness trajectory and progression. 8 11 Notwithstanding, the mediators of the association between obesity and adverse brain function are insufficiently characterized. Replicated evidence suggests that the metabolic–immunoinflammatory interface is a critical moderator of the differential effects of obesity on individuals with a neuropsychiatric illness.…”
Section: Introductionmentioning
confidence: 99%
“… 16 Moreover, the convergence of replicated evidence indicating that overweight/obesity influences structural and functional changes in patients with neuropsychiatric disorders (eg, anxiety and depression), provides a basis for hypothesizing that overweight/obesity alters brain structure and function, increasing the brain’s propensity toward disturbances in mood and cognition. 8 , 16 18 …”
Section: Introductionmentioning
confidence: 99%
“…Although in adults with schizophrenia, BDNF has been associated with cortical thickness 20,46 and hippocampal volume, 21 the literature investigating the relationship between peripheral concentrations of BDNF and brain structures in children and adolescents remains scant. Although an association between peripheral BDNF concentrations and brain volumes and cortical areas was observed in a study of bipolar offspring and healthy controls, 19 another study did not find differences between BDNF serum concentrations and hippocampal volume in children and adolescents diagnosed with bipolar disorder. 22 Table 1.…”
Section: Discussionmentioning
confidence: 82%
“…21 However, other studies of individuals with bipolar disorder showed no correlation between BDNF concentrations and hippocampal volumes in children, 22 and no association between BDNF and gray matter volumes in adults. 23 In 1 study, peripheral BDNF concentrations and brain volumes (including cortical areas) were correlated negatively in bipolar offspring but positively in healthy controls 19 ; suggesting the need for larger studies investigating interactive effects between psychopathology and serum BDNF in predicting brain volumes.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation